Deconstructing My Library, Unwrapping My Lifeworld - Coetzee, Jan K. (Qualitative Sociology Review, 2019)
One of the most frequent ways of narrating everyday life in developed countries has been via the printed book. The invention of printing allowed for an ever-increasing mass production of documents of life that systematically established an era of communication and a political economy that had profound implications for the structure of living together. This article departs from the context of my own lifeworld: a lifeworld closely related to printed books. When attempting to explore and understand the overt and covert meanings embedded in the historical development of our social lives and the objects around us, we can turn for assistance to an analysis of the books on our shelves, books that have been constant companions for long periods of our lives. In this article, I propose that any valid interpretation, understanding, and depiction of social reality need to be, in essence, autobiographical. The autobiographical account I present includes how my personal life trajectory led me to the books that surround me. And how, in turn, these books become a reflection of myself and my roots.